2017
DOI: 10.3390/s17112614
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Heavy-Metal Ions of Unfolded Fullerene Quantum Dots

Abstract: A novel type of graphene-like quantum dots, synthesized by oxidation and cage-opening of C60 buckminsterfullerene, has been studied as a fluorescent and absorptive probe for heavy-metal ions. The lattice structure of such unfolded fullerene quantum dots (UFQDs) is distinct from that of graphene since it includes both carbon hexagons and pentagons. The basic optical properties, however, are similar to those of regular graphene oxide quantum dots. On the other hand, UFQDs behave quite differently in the presence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 62 publications
5
34
0
Order By: Relevance
“…The fluences were in the 0.1-100 µJ/cm 2 range. The excitation spectra were recorded using a conventional 90 • geometry on a dedicated laboratory setup equipped with a 200 W continuous Hg(Xe) discharge lamp (Oriel instruments, Stratford, CT, USA), an excitation 25-cm monochromator (Photon Technology International, Inc., Birmingham NJ, USA) and an emission 25-cm monochromator (Cornerstone 260, Stratford, CT, USA) equipped with specific excitation-rejection filters and a R3896 photomultiplier (Hamamatsu Photonics Corp., Bridgewater, NJ, USA) [30,31].…”
Section: Spectral Measurementsmentioning
confidence: 99%
“…The fluences were in the 0.1-100 µJ/cm 2 range. The excitation spectra were recorded using a conventional 90 • geometry on a dedicated laboratory setup equipped with a 200 W continuous Hg(Xe) discharge lamp (Oriel instruments, Stratford, CT, USA), an excitation 25-cm monochromator (Photon Technology International, Inc., Birmingham NJ, USA) and an emission 25-cm monochromator (Cornerstone 260, Stratford, CT, USA) equipped with specific excitation-rejection filters and a R3896 photomultiplier (Hamamatsu Photonics Corp., Bridgewater, NJ, USA) [30,31].…”
Section: Spectral Measurementsmentioning
confidence: 99%
“…As stated in our previous works [27,28,37] we reported different studies about the interaction between UFNPs and heavy metal ions. Due to an aggregation process, the interaction of heavy metal ions and UFNPs can cause the formation of a stable complex [37,38].…”
Section: Figure 6 Response In the Presence Of Different Heavy Metal Imentioning
confidence: 78%
“…Different responses were obtained depending on the starting materials, the dimension of GOQDs, the number of functional groups on the edge and on the surface and so on. For example, responses to a number of heavy metal ions have been analyzed starting by exfoliated graphite using modified Hummer method [4,11], or by using pyrolysis of citric acid [12] or chemical oxidation of carbon fibers [16], or Hummer method starting from C 60 fullerene [27,28]. The results were sometime not comparable and a dependence on synthetic method of production of GOQDs was observed that suggest the need of further studies.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the aforementioned methods, fluorescence analysis has attracted considerable attention due to its relatively low cost, high sensitivity, ease of operation, reliable approach and its low detection limit [ 12 ]. Recently, fluorescent carbon nanodots (FCNs), a new class of carbon nanomaterials, have been actively researched and well applied in biosensors, biomarkers, biomedical imaging and so on [ 13 , 14 , 15 , 16 , 17 ]. In striking contrast to semiconductor quantum dots, FCNs are superior fluorescent nanomaterials due to their low toxicity, high chemical stability and low environmental impact.…”
Section: Introductionmentioning
confidence: 99%